INOVASI SEDIAAN ORAL FISETIN DENGAN TEKNOLOGI SMART EDIBLE PAPER - Dzakwan, Muhammad (P3M STIKes Bakti Tunas Husada, 2019)
Fisetin is a flavonoid compound has natural antioxidant, anti-inflammatory and anticancer activities. It hasvery low bioavailability and the provision of fisetin in the oral dosage form is very limited. Research has beencarried out to develop and increase solubility and dissolution of fisetin. It was further developed into a solidoral dosage form of tablets with an edible paper matrix. This study that to develop fisetin into tablet dosageform with an edible paper matrix, determine the physical quality of tablets and drug release in vitro. Fisetin wasdissolved in a suitable solvent and then poured over an edible paper matrix, dried and cut in 1x1 cm size. Papercuttings are printed directly with various compressive strengths of 2, 4 and 6 tons. Tablet physical quality testsinclude hardness, disintegration time, friability, weight uniformity, and drug content. Furthermore, dissolutionwas tested and the best formula was chosen. The results of this research show that fisetin has the greatestsolubility with DMSO solvent. The edible paper matrix weight is 1000 mg and a tablet weight is 500 mg.Formula I with a compressive strength of 2 tons is the best formula and meets the physical quality testrequirements of the tablet. The release of formula I (FI) drug was superior (95.20%) and significantly higher(p<0,05) compared to formula II and III.